Simulation and Reverse Design of the Cam-Gear Combination Mechanism with the Given Movement - Xu Long (Jixie chuandong)
The research of the cam- gear combination mechanism,according to the given trajectory,the design is divided into two parts reverse solution cam meshing track and cam outline. Based on the cam meshing track reverse solution with SOLIDWORKS software and the MOTION plug- in,through the EXCEL software for data processing,the ideal cam outline is acquired and making the mechanism can realize given trajectory,the correctness of the design is verified by forward simulation. This solution method is concise and accurate,the tedious computation is eliminated,it is suitable for engineering people.